Stock Selection and Market Timing Ability to Increase Indonesia's Equity Mutual Fund Performance - Sihombing, Pardomuan; Manurung, Arifin Hasudungan; Zakchona, Elia (Jurnal Keuangan dan Perbankan, 2023)
This study investigates the effect of stock selection, market timing, and fund size on the mutual fund’s performance with Covid-19 as a moderating variable. The sample data is limited to the listed conventional mutual funds supervised by the financial service authorization from 2014 to 2021, denominated in Rupiah currency, have a complete report, and have more than Rp 350 billion in fund equities. The sample data implements twenty-eight of the listed conventional mutual funds and is examined by a random method of Panel data multi-regression with moderated regression analysis (MRA). The result shows that market timing positively affects, and Covid-19 can enhance the effect of stock selection on the mutual fund’s performance. Meanwhile, stock selection, fund size, and Covid-19 do not affect the mutual fund’s performance. Covid-19 cannot moderate the effect of market timing and fund size on the mutual fund’s performance. Fund managers highlight market timing as a crucial indicator of obtaining more returns, and Covid-19 is the best moment to select and collect potential stock at affordable prices and trade them to get more returns after the crisis. DOI: 10.26905/jkdp.v27i4.11047